A single layer of Fe3O4@TiO2 submicron spheres as a high-performance electrode for lithium-ion microbatteries. Issue 10 (2nd August 2019) - Kim, Jung-Min; Hwang, Jun-Ki; Sun, Yang-Kook; Hassoun, Jusef
Abstract : High-capacity electrodes with an ultrathin layer configuration represent a suitable component for modern microbatteries. Abstract : High-capacity electrodes with an ultrathin layer configuration represent a suitable component for modern microbatteries. Herein, we report a simple approach consisting of spin-coating and subsequent heat treatment to achieve a single-layer electrode of Fe3 O4 @TiO2 core–shell submicron spheres. The single-layer electrode operates via conversion and insertion reactions with lithium, which are favored by a thin carbon interlayer between the active particles and the copper substrate, without any polymeric binder or nanosized conductive additive. The lithium-ion reaction kinetics and charge transfer characteristics are enhanced by the fine morphological tuning of the electrode particles as well as by the thin carbon interlayer. Indeed, lithium cells using the Fe3 O4 @TiO2 core–shell submicron spheres and thinnest carbon interlayer exhibit a life that extends over 400 cycles with excellent capacity retention and very high rate capability. These characteristics facilitate the application of the proposed electrode in high-performance Li-ion microbatteries.